2022
DOI: 10.1155/2022/1777187
|View full text |Cite
|
Sign up to set email alerts
|

Study on Leaching of Phosphate from Municipal Wastewater Treatment Plant’s Sewage Sludge and Followed by Adsorption on Mg‐Al Layered Double Hydroxide

Abstract: Sewage sludge from municipal wastewater treatment plant was a rich phosphorus resource. In this study, HCl, H2SO4, and HNO3 were investigated as leaching acids for extraction of phosphate from the sludge to recover this value nutrient by adsorption using layered double hydroxide (LDH) nanomaterial. Mg-Al LDH was synthesized by coprecipitation at room temperature and at a constant pH of 10 (±0.5) with Mg/Al molar ratio of 2.0. The material was characterized by scanning electron microscopy (SEM), X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…101 Based on the data presented in Tables 3 and 4, it can be deduced that acid treatment of hydrochar allows for a significant recovery of P that can reach 100% depending on the utilized acid, and that can mainly be attributed to the effect of increasing H + activity on the solubility of P. High acid concentrations tend to increase the efficiency of P extraction from hydrochar, while HCl and citric acid appear to be the most effective among different acids. These findings agree with the experimental results of Phuong et al (2022), where the efficiency of different acids in P-leaching was assessed. Their results showed that, for samples with moderately high moisture levels, the increase in acid concentration for HCl and H 2 SO 4 leads to a significant increase in P-leaching.…”
Section: Applied P-recovery From Htc P-recovery From Hydrocharsupporting
confidence: 91%
See 2 more Smart Citations
“…101 Based on the data presented in Tables 3 and 4, it can be deduced that acid treatment of hydrochar allows for a significant recovery of P that can reach 100% depending on the utilized acid, and that can mainly be attributed to the effect of increasing H + activity on the solubility of P. High acid concentrations tend to increase the efficiency of P extraction from hydrochar, while HCl and citric acid appear to be the most effective among different acids. These findings agree with the experimental results of Phuong et al (2022), where the efficiency of different acids in P-leaching was assessed. Their results showed that, for samples with moderately high moisture levels, the increase in acid concentration for HCl and H 2 SO 4 leads to a significant increase in P-leaching.…”
Section: Applied P-recovery From Htc P-recovery From Hydrocharsupporting
confidence: 91%
“…(2022), where the efficiency of different acids in P‐leaching was assessed. Their results showed that, for samples with moderately high moisture levels, the increase in acid concentration for HCl and H 2 SO 4 leads to a significant increase in P‐leaching 116 …”
Section: Applied P‐recovery From Htcmentioning
confidence: 99%
See 1 more Smart Citation
“…Several phosphate detection techniques, such as spectrophotometry, fluorometry and chromatography, are available. However, their time-consuming, labor-intensive and costly characteristics, dependence on skilled operators and hazardous chemicals, make them inappropriate for monitoring purposes [3,4]. Separation or isolation of large radii anions from water such as phosphate requires other suitable materials that are unavailable.…”
Section: Introductionmentioning
confidence: 99%